State-Building: Die Rolle von Streitkräften am Beispiel der Bundeswehr in Afghanistan - Bartscher, Michael, M.A. (Nomos Verlagsgesellschaft mbH & Co. KG, 2024)
As a result of the terrorist attacks of 11th September 2001, the United States declared the fight against terror and the elimination of al-Qaeda in Afghanistan as its primary goals. After a quick victory over the Taliban, a sovereign democratic state was to be created in Afghanistan in conjunction with security sector reform. The Federal Republic of Germany's involvement in the Afghanistan mission marked a turning point in international crisis management. This book examines the effectiveness of the Bundeswehr's activities in reforming the Afghan security sector in cooperation with other national departments and alliance partners.